Study of Replanting Program of Smallholder Oil Palm in Jambi Province - Sri Gunawan; M. Adi Putra Fajar Islami (Oil Palm Research and Review, 2021)
Replanting of smallholder oil palm plantations is carried out to replace plants that have passed the economic age of 25 years and / or plants whose productivity is less than or equal to 10 tonnes of FFB / ha/year. In order for this replanting policy to be realized, support for the development of human resources is needed to increase the knowledge, skills, and abilities of farmers in carrying out sustainable oil palm cultivation and to grow, develop and strengthen smallholder institutions. This study aimed to analyse the readiness of farmers for oil palm replanting programs. The data used in this study are primary data and secondary data. Primary data collection techniques obtained through direct interviews with respondent farmers using a questionnaire and direct observation. Secondary data is obtained from data on the agronomic character of oil palm and related institutions or agencies such as the plantation office and BP3K as well as other literature such as journals, theses, publications, and other literature related and relevant to the research. From this research, information regarding the replanting model, replanting cost, and agronomic character carried out by the farmers will be obtained.